On some factors that may affect the birth weight of babies born at Base Hospital, Avissawella. - Ibralebbe, M.S (My University, 1995)
This study was undertaken to determine the incidence and the short term clinical implications of urinary bladder dysfunction and to assess what maternal , fetal and obstetric risk factors are associated with it. In addition, the validity and the reliability of the ultrasonic assessment of the post void bladder volume was objectively evaluated . In order to achieve these objectives a prospective observational study was done at a University affiliated maternity ward in a tertiary care hospital. The study population comprised 605 consecutive , unselected mothers who had delivered vaginally. Computer based statistical packages were used in the analysis of data, and non-parametric tests were deployed as the data did not show a normal distribution. Ultrasonic measurements and urethral catheter estimates exhibited a strong positive linear relationship. 33 percent patients ( of 5.45 percent) were diagnosed with post partum voiding dysfunction. Of the Possible risk factors that were under evaluation prim parity, long duration of labour, increased birth weight, instrumental delivery, and perineal trauma were found to have a positive linear relationship with post void bladder volumes, while maternal age, BMI and POA did not show such a relationship. Short term follow up the patient diagnosed with post partum bladder dysfunction on the basis of abnormal voiding parameters did not show emergencies of new symptoms of voiding dysfunction and the abnormal bladder volumes were noted to resolve spontaneously with time. It was concluded that trend abdominal ultrasound scan is a reliable alternative to urethral catheterization in the Measurement of the post partum post void bladder volume.